The relationship between baseline nutritional status with subsequent parenteral nutrition and clinical outcomes in cancer patients undergoing cytoreductive surgery: a retrospective study - AlTawil, Esraa; Kalagi, Nora A.; Alzahrani, Sohailah; Alobeed, Faisal; Alshammari, Sulaiman; Bin Traiki, Thamer (Frontiers in Nutrition, 2024)
Hyperthermic Intraperitoneal Chemotherapy (HIPEC) with Cytoreductive Surgery (CRS) is the preferred treatment for peritoneal malignancies. This highly complex operation is associated with a high incidence of complications, particularly due to malnutrition. This study aimed to investigate the potential association between preoperative nutritional status and postoperative clinical outcomes in adult cancer patients who underwent CRS/HIPEC for peritoneal malignancy. A retrospective study with 140 adult cancer patients, on parenteral nutrition (PN) (n=40) and not on PN (n=100) who underwent CRS with or without HIPEC, was conducted. Patients who received PN had significantly longer post-operative, hospital, and ICU LOS than those who did not (P=0.001). ICU admission was significantly higher in the non-PN receiving group compared to the PN receiving group. When compared to the PN group, the majority of patients not receiving PN were at low risk of malnutrition (91% vs 75%, P=0.020), whereas 17.5% of PN patients were at risk of malnutrition during hospitalization. Multiple regression analyses revealed a strong positive relationship between patients with increased risk of malnutrition and ICU LOS (p=0.047). Routine preoperative nutrition assessment is essential to identify patients who are at higher nutritional risk, and nutrition support should be provided preoperatively.